2016
DOI: 10.1038/srep28508
|View full text |Cite
|
Sign up to set email alerts
|

The 14th Ile residue is essential for Leptin function in regulating energy homeostasis in rat

Abstract: LEPTIN (LEP) is a circulating hormone released primarily from white adipocytes and is crucial for regulating satiety and energy homeostasis in humans and animals. Using the CRISPR technology, we created a set of Lep mutant rats that carry either null mutations or a deletion of the 14th Ile (LEP∆I14) in the mature LEP protein. We examined the potential off-target sites (OTS) by whole-genome high-throughput sequencing and/or Sanger-sequencing analysis and found no OTS in mutant rats. Mature LEP∆I14 is incessantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…We previously generated Leptin deficient (Lep ∆I14/∆I14 ) rats by CRISPR technology. (14) Interestingly, we found that Lep ∆I14/∆I14 rats display distinctive NASH phenotypes, which needs to be further characterized.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…We previously generated Leptin deficient (Lep ∆I14/∆I14 ) rats by CRISPR technology. (14) Interestingly, we found that Lep ∆I14/∆I14 rats display distinctive NASH phenotypes, which needs to be further characterized.…”
Section: Introductionmentioning
confidence: 80%
“…Lep ∆I14/∆I14 rats share many similar phenotypes with ob/ob mice, such as obesity, hyperglycaemia, hyperinsulinemia, NAFLD, and infertility. (14) Our previous histopathological examination showed that NAFLD starts at postnatal week 8. (14) Consistently, body weight and relative liver weight of Lep ∆I14/∆I14 rats were significantly higher than those of their wild-type (WT) littermates after 8 postnatal weeks (fig.…”
Section: Leptin Deficiency Leads To Nash Phenotypes In Ratsmentioning
confidence: 99%
“…1 ). We created Tshr mutant rats by CRISPR/Cas9 gene editing tool following the protocol as previously reported 15 . Briefly, we designed two specific targeting sequences in the 10th exon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rat is bigger in size than mouse so that to provide larger amount of blood/tissue samples for accurate assessment. Moreover, rat is more physiologically similar to human 14 and thus shows similar phenotypes to those in human which sometimes are not seen in the mouse counterpart 15 . Taking advantage of the CRISPR gene-editing technology, we sought to develop a novel rat model to functionally characterize the truncated Tshr protein in vivo .…”
Section: Introductionmentioning
confidence: 90%
“…csiro.au/; Supplemental Table S1). The plasmid construction, in vitro transcription, and subsequent 1-cell embryo injection were performed following previous protocols by Xu et al (36). The mixture of single-guide RNA (sgRNA; 50 ng/ml) and Cas9 mRNA (100 ng/ml) were injected into the cytoplasm of 1-cell embryos at the pronucleus stage.…”
Section: Human Lung Cancer Tissue Specimensmentioning
confidence: 99%